What does it take? A CB-SEM Study on Game Motivation for E-sports Players in India - Panwar, Tapish (Sport, Business and Management: an International Journal, 2025)
The emergence of E-sports as a major sporting category has led to a rise in global research on player motivation, The existing studies point towards a market-based skewness accentuated by demographic variation warranting market-specific research. This study attempts to address this challenge owing to the lack of research on player motivation for e-sports in India Design/methodology/approach The study draws factors of motivation from foundational theories in self-gratification and player motivation. The survey was conducted using an online questionnaire sent across various channels including social media, and also using snowballing. Measurement models were tested using confirmatory factor analysis (CFA) (n-423) and PLS-SEM (n-423) was used for ultimate path analysis and hypothesis testing Findings The findings suggest that e-sports players in India are driven by achievement due to the feeling of competition and advancement in the game. The ability to socialise and work in teams further extends this motivation. Finally, discovering newer game elements and a sense of escaping reality adds to the list of gratification that motivates the players. The demographic and usage behaviour points towards a significant shift in the Indian e-sports Industry. Originality/value This study investigates player motivations based on perceived gratification - achievement, socialising, and immersion, drawn from Bartle's player types for Indian e-sports players. The study shall help game developers and league owners by targeting specific sub-components of motivation more effectively to enhance player experience thus increasing engagement and retention.
ISME
Keywords: E-sports; Motivation; Escapism; Immersion; Socialising; Achievement; Video Games; Online Gaming; India E-sports